2020
DOI: 10.1002/agj2.20257
|View full text |Cite
|
Sign up to set email alerts
|

Soil and crop management systems that ameliorate damage caused by decades of dryland agroecosystem mismanagement

Abstract: Sustainable crop production in the Great Plains of North America has been challenging since early settlement times, and mismanagement has severely damaged our dryland agroecosystems. The unintentional damage stemmed from using practices unsuited to dryer climates. In fact, the management practices imported from more humid agricultural areas during the settlement period were considered the best ways to farm. The Dust Bowl era was the disastrous result of creating bare soil surfaces, with aggregates pulverized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…In the semiarid climate of the High Plains region of the United States, dryland grain farmers often include unvegetated fallow periods in their crop rotations to replenish moisture in the soil profile. Winter wheat ( Triticum aestivum L.)–fallow cropping has resulted in soil degradation since organic inputs are periodic and erosion during fallow periods can occur when there is reduced ground cover (Peterson et al., 2020; Rosenzweig et al., 2018). Understanding the temporal effects of these fallows on SOM dynamics is critical for managing and building SOM stocks on dryland farms.…”
Section: Introductionmentioning
confidence: 99%
“…In the semiarid climate of the High Plains region of the United States, dryland grain farmers often include unvegetated fallow periods in their crop rotations to replenish moisture in the soil profile. Winter wheat ( Triticum aestivum L.)–fallow cropping has resulted in soil degradation since organic inputs are periodic and erosion during fallow periods can occur when there is reduced ground cover (Peterson et al., 2020; Rosenzweig et al., 2018). Understanding the temporal effects of these fallows on SOM dynamics is critical for managing and building SOM stocks on dryland farms.…”
Section: Introductionmentioning
confidence: 99%
“…1; Unger & Baumhardt, 2001). As in other dryland regions, soil water availability is the single most limiting factor affecting crop production (Peterson, Westfall, Schipanski, Fonte, 2020).…”
Section: Challenges Of Dryland Agriculture In the Us Great Plainsmentioning
confidence: 99%
“…In the early 20 th century, agriculturalists advised farmers to stabilize winter wheat yields by implementing fourteen months of bare fallow to store water in the soil before planting (Peterson et al 2020). Decades of research have shown, however, that the fallow does not store water efficiently (Nielsen and Vigil 2010).…”
Section: Eliminate County-level Fallow Requirements For Wheat To Promote Soil Health and Crop Diversificationmentioning
confidence: 99%
“…The rise of no-till farming, in which the crops are planted without plowing, has allowed many farmers to plant a productive crop annually without summer fallow periods. This practice thus protects soil from erosion, increases soil carbon, and leads to greater overall yield and income (Peterson et al 2020;Rosenzweig, Fonte, and Schipanski 2018). The adoption of more frequent and diverse cropping practices, however, has been hindered by FCIP policy that requires fallow prior to sowing wheat to insure the crop (Rosenzweig, Carolan, and Schipanski 2019).…”
Section: Eliminate County-level Fallow Requirements For Wheat To Promote Soil Health and Crop Diversificationmentioning
confidence: 99%